THE IMPACT TAX KNOWLEDGE, TAX AWARENESS, TAX MORALE TOWARD TAX COMPLIANCE BOARDING HOUSE TAX - Hantono (International Journal of Research -GRANTHAALAYAH, 2021)
This study aims to determine the effect of 1) tax knowledge, 2) tax awareness, 3) tax morale, 4) tax compliance. The sampling in this research was conducted by using an incidental sampling method. Methods of data collection through questionnaires that have been distributed to 100 respondents who have met the criteria. Multiple linear regression analysis shows that tax knowledge, tax awareness, and tax morale are significant toward tax compliance. The simultaneous have a significant effect on tax compliance. It can be concluded that tax knowledge mitigation, tax awareness, and tax morale towards tax compliance. The results of t-test showed that tax knowledge isn’t approved and indicates it has a significant impact on affecting tax compliance, tax awareness is approved, and indicates has less impact on affecting tax compliance, tax morale isn’t approved. It indicates has a great impact on affecting tax compliance. The results of F test showed that both of the independent variables are simultaneously affecting tax compliance. R Square’s result is 0.710, which shows that 71 % of tax compliance mitigation can be explained by tax knowledge, tax awareness, and tax morale. Simultaneously, 29 % of tax compliance variables can be explained by other factors or variables not examined in this research.